Arrested Welcome : Hospitality in Contemporary Art - Aristarkhova, I. (Irina) (Book collections on Project MUSE., 2020)
"In The Art of Welcome: Hospitality in Contemporary Art, Irina Aristarkhova discusses lessons in hospitality that contemporary artists teach their audiences, specifically focusing on fears and anxieties of more challenging situations of hospitality. "Hospitality," as a practice of welcoming others, has increasingly become a central, albeit contested, concept, in academic, cultural, and public spheres. The Art of Welcome theorizes practices of hospitality in contemporary art drawing on art works by Lee Mingwei (Taiwan/USA), Kathy High (USA), Pippa Bacca and Silvia Moro (Italy), Faith Wilding (USA), Ana Prvacki (Singapore/Serbia/Germany), and Mithu Sen (India)"--